BRAND IMAGE MELALUI CUSTOMER SATISFACTION SEBAGAI VARIABEL INTERVENING TERHADAP CUSTOMER LOYALTY PADA PRODUK SKINCARE SAFI INDONESIA - Niswatul Ma'azah; Ari Prasetyo (Airlangga Journal of Innovation Management, 2023)
The increasing Muslim population and the trend of halal living in Indonesia have made competition between skincare product brands in Indonesia increasingly fierce. Safi skincare products are one of the brands that has an Islamic brand image and emphasizes halal products. This research was conducted to determine the influence of brand image on customer loyalty with the mediating effect of customer satisfaction on Safi Indonesia skincare products. The target of this research is Safi Indonesia skincare consumers. This research used a sample of 175 consumers who had purchased Safi skincare products, using the SEM-PLS analysis technique. The results of this research show that brand image has a significant relationship with customer loyalty, brand image has a significant relationship with customer satisfaction, customer satisfaction has a significant relationship with customer loyalty, then brand image has a significant relationship with customer loyalty with customer satisfaction as a mediating effect. This research can be used as a guide or reference for research related to the same field as well as being a source of knowledge for comparison of existing theories.